(untitled) (Panacea Journal of Medical Sciences, 2024)
Introduction: Preeclampsia is one of the common medical complications during pregnancy and is one of the top five causes of maternal death in the world. Preeclampsia is defined as development of hypertension, proteinuria and edema at or after 20 weeks of gestation. The main aim of this study was to estimate and compare levels of adenosine deaminase (ADA) and C- reactive protein (CRP) in serum of preeclampsia and normotensive pregnant women. Materials and Methods: This case control study included 120 subjects who were pregnant and in the age group of 19-35 years. 60 preeclampsia patients were taken as cases and 60 age matched healthy primigravida as controls. After obtaining ethical clearance and taking informed consent, ADA and CRP levels were analysed. Serum CRP was estimated by immunoturbidimetric method and ADA was estimated by colorimetric method on a spectrophotometer. Results are expressed as mean±SD. Comparison of two study groups was done using unpaired student’s t test. A p value of less than 0.05 was considered significant. Results: There was significant increase in the serum levels of ADA and CRP in cases of preeclampsia in comparison to normotensive pregnant women. Conclusion: Elevated levels of serum ADA suggests the role of probable decreased cell mediated immunity in normal pregnancy and increased cell mediated immunity in preeclampsia. Increased CRP levels reflect the inflammatory response in progression of disease. Estimation of ADA and CRP parameters is inexpensive and can be of some diagnostic and prognostic significance in preeclampsia.